2022
DOI: 10.1021/acsabm.2c00165
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Solute Transport in Supramolecular Hydrogels Spanning Dynamic to Quasi-Static States

Abstract: Hydrogels prepared from supramolecular cross-linking motifs are appealing for use as biomaterials and drug delivery technologies. The inclusion of macromolecules (e.g., protein therapeutics) in these materials is relevant to many of their intended uses. However, the impact of dynamic network cross-linking on macromolecule diffusion must be better understood. Here, hydrogel networks with identical topology but disparate cross-link dynamics are explored. These materials are prepared from cross-linking with host–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The discrepancy between our in vivo and in vitro results highlights the inability of in vitro release assays to adequately model the in vivo environment. Many other studies investigating supramolecular hydrogel drug delivery have seen similar discrepancies between in vitro and in vivo release kinetics. ,, The results of the current study and these related investigations demonstrate that the complex biological environment (complete with proteins, cells, etc.) plays a large role in governing the release kinetics from supramolecular materials.…”
Section: Resultssupporting
confidence: 71%
“…The discrepancy between our in vivo and in vitro results highlights the inability of in vitro release assays to adequately model the in vivo environment. Many other studies investigating supramolecular hydrogel drug delivery have seen similar discrepancies between in vitro and in vivo release kinetics. ,, The results of the current study and these related investigations demonstrate that the complex biological environment (complete with proteins, cells, etc.) plays a large role in governing the release kinetics from supramolecular materials.…”
Section: Resultssupporting
confidence: 71%
“…Dynamic crosslinks have also been investigated for particle transport via simulations, and it was found that diffusion can be greatly accelerated when bonds can exchange in the network. 46 Recently, it has been shown how hydrogels with dynamic bonds can influence macromolecular solute transport 47 and how protein diffusion through rigid DNA networks is impacted by dynamic exchange. 48 However, experimental tests of how dynamic bonds control molecular transport in dense, dry systems are currently lacking.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To gain insight into the relationship between hydrogel mesh size and protein release profiles we calculated the approximate mesh size of each hydrogel from the average storage moduli ( G ′) using eq 1 as previously reported by Shibayama 50 and Webber (see the Materials and Methods section and Table S4 in the Supporting Information for calculated mesh size values). 49 For NaCl hydrogels, the mesh size slightly increases in the following order: TI (9.0 nm) < RNase A (14.3 nm) < BSA (15.4 nm) < human IgG (17.0 nm). Although this trend is inversely proportional to G ′ ( Table S4 ), there is no clear correlation between the release profiles and rate of diffusion with the calculated mesh sizes.…”
Section: Resultsmentioning
confidence: 96%
“…The mesh size of the hydrogel network is also likely to influence the release rates of proteins from these hydrogels, with smaller proteins released at more rapid rates. To gain insight into the relationship between hydrogel mesh size and protein release profiles we calculated the approximate mesh size of each hydrogel from the average storage moduli ( G ′) using eq as previously reported by Shibayama and Webber (see the Materials and Methods section and Table S4 in the Supporting Information for calculated mesh size values) . For NaCl hydrogels, the mesh size slightly increases in the following order: TI (9.0 nm) < RNase A (14.3 nm) < BSA (15.4 nm) < human IgG (17.0 nm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation